ANALISIS DAMPAK GLOBALISASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Herlin Putri Emilia; Timbul Dompak (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2024)
This study examines the impact of globalization on Indonesia's economic growth, focusing on both positive and negative impacts. Globalization, characterized by the integration of global markets, has enabled Indonesia to participate in international trade, attract foreign direct investment (FDI), and access advanced technology, all of which contribute to economic expansion, especially in the manufacturing, technology, and infrastructure sectors. This research employs descriptive analysis using secondary data from reliable sources such as the World Bank, Bank Indonesia, and the Central Statistics Agency (BPS). All studies show that FDI and economic growth have significantly increased Indonesia's GDP, created employment opportunities, and expanded local industries. However, globalization has also had negative impacts, such as environmental degradation caused by the exploitation of natural resources, a growing economic gap between rural and urban areas, and the decline of local culture. This study highlights the need for policies that support the growth of local industries, particularly small and medium- enterprises (“UKM”), while protecting the environment and upholding Indonesian culture. The study shows that while globalization offers significant opportunities for economic growth, strategic governance is needed to mitigate its negative impacts and ensure inclusive and sustainable growth.